NAD+ DEPLETION AS A CAUSE OF INFLAMMAGING. (11th November 2018) - Schultz, M B; Bochaton, T; Bonkowski, M; Li, J; Lokitiyakul, D; Colville, A; Gomes, A; Sinclair, D
Abstract: Chronic inflammation, in the absence of infection, is a conserved characteristic of aging. Such inflammation underlies susceptibility to many age-related diseases including cancer, diabetes, and neurodegenerative disorders, and limits longevity. However, the causes of age-related chronic inflammation, also known as "inflammaging", are not well understood. Levels of the metabolite NAD+ decline with age and promote inflammation through multiple mechanisms, including by limiting the activity of sirtuins and poly-ADP-ribose polymerases (PARPs). Interestingly, in bone marrow-derived macrophages and immortalized RAW264.7 mouse macrophages, NAD+ levels rapidly fall upon exposure to the pro-inflammatory stimulus LPS. This loss is due to consumption of the metabolite, rather than reduction, as levels of NADH also decline. We have implicated members of the PARP family as the cause of declining NAD+ during inflammation, and hypothesize that this NAD+ loss promotes inflammation during aging. To understand the effects of declining NAD+, we have treated macrophages with NAD+-precursors and PARP inhibitors, which limit the LPS-driven NAD+ loss. These molecules the secretion of cytokines, and may reduce DNA damage and NLRP3 inflammasome activation. We hypothesize that low NAD+ promotes age-related inflammation, and may be a target for pharmacological intervention. United States